Analisis pembelajaran daring siswa sekolah menengah atas di Kecamatan Mranggen kelas XI di tengah Pandemi Covid-19 - Jayanti Gustia Wulandari (Journal of Physical Activity and Sports (JPAS), 2021)
This research is motivated by the Covid-19 pandemic in Indonesia which has an impact on the economic inequality of society and also the impact of education which hinders the learning process. This has led to a new learning method called online learning or distance learning which is now being implemented by the government. Students are required to take online learning because the Covid-19 pandemic does not allow students to take face-to-face learning with the teacher. The purpose of this study is to analyze online learning in Upper Middle School Students in the Mranggen District. The method used in this research is the descriptive qualitative method. Test the validity of the data using validity and credibility tests. The data analysis used is reduction, display data, and conclusion drawing/verification. The results of this study indicate that online learning or distance learning has many advantages and disadvantages experienced by students, parents, and physical education teachers in SMA Mranggen District. In its strength, students know more about information technology or what is called IT. The drawback of online learning itself is that the limited facilities and infrastructure that are owned by the teacher and students make learning less optimal. The conclusion of this research is that research can get results that the Covid-19 pandemic has advantages and disadvantages of online learning from Physical Education and Health in Mranggen District.